Chameleons on the racetrack - Nastase, Horatiu [UNESP]; Weltman, Amanda (Springer Nature, 2013)
We modify the ansatz for embedding chameleon scalars in string theory proposed in [1] by considering a racetrack superpotential with two KKLT-type exponentials e ia instead of one. This satisfies all experimental constraints, while also allowing for the chameleon to be light enough on cosmological scales to be phenomenologically interesting. © 2013 SISSA, Trieste, Italy.
Keywords: Cosmology of Theories beyond the SM; dS vacua in string theory; Supergravity Models